THE IMPORTANCE OF LOGISTICS AND SUPPLY CHAINS FOR PANDEMIA CONDITIONS - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2020)
The COVID-19 pandemic has introduced an unprecedented amount of uncertainty into the global economy as countries around the world battle growing troubles, implement broad social distancing strategies, and seek fiscal interventions to stabilize markets. What about logistics and supply chains in the market? Is there an impact of the COVID-19 virus on logisticians' obligations when securing market requirements in accordance with international business standards? Most entities have focused their attention on protecting employees, perceiving and managing risks that are threatening to business, and managing supply chain downtime due to efforts to curb the spread of virus coronas. The pervasive impact, now pandemic, on businesses and supply chains will be clearer in the coming period, while global economic recovery will depend on the impact of the affected countries to cope with the effects of the virus.
Keywords: logistics; supply chains; market